2011
DOI: 10.1158/1078-0432.ccr-10-0081
|View full text |Cite
|
Sign up to set email alerts
|

KPNA2 Expression Is an Independent Adverse Predictor of Biochemical Recurrence after Radical Prostatectomy

Abstract: Purpose: To analyze rates of expression of karyopherin alpha 2 (KPNA2) in different prostate tissues and to evaluate the prognostic properties for patients with primary prostate cancer.Experimental Design: Tissue microarrays (TMA) contained 798 formalin-fixed, paraffin-embedded prostate tissue cores from two different institutes of pathology. TMAs were stained immunohistochemically for KPNA2 and NBS1. SiRNA technologies were used to inhibit KPNA2 expression in vitro, and the effect of this inhibition on cellul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
104
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(116 citation statements)
references
References 28 publications
10
104
2
Order By: Relevance
“…Although we do not have direct data showing the precise role of KPNA2 in glioma, based on the improved outcomes in patients exhibiting elevated expression of MIR517C, we hypothesize that KPNA2 may act as an oncogene in GBM. These findings are supported by a study by Gousias et al, 46 who show that patients with astrocytoma who exhibit higher expression of KPNA2 have poorer prognoses and increased resistance to chemotherapy, suggesting that KPNA2 may be a diagnostic and prognostic marker for astrocytoma.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although we do not have direct data showing the precise role of KPNA2 in glioma, based on the improved outcomes in patients exhibiting elevated expression of MIR517C, we hypothesize that KPNA2 may act as an oncogene in GBM. These findings are supported by a study by Gousias et al, 46 who show that patients with astrocytoma who exhibit higher expression of KPNA2 have poorer prognoses and increased resistance to chemotherapy, suggesting that KPNA2 may be a diagnostic and prognostic marker for astrocytoma.…”
Section: Discussionsupporting
confidence: 73%
“…As a member of the karyopherin family, KPNA2 has been investigated as a promising biomarker and prognostic factor in several types of solid tumors, including breast cancer, ovarian cancer, prostate cancer, and melanoma. [43][44][45][46] In our study, KPNA2 was found to be a direct target of MIR517C, and overexpression of KPNA2 blocked the function of MIR517C. Although we do not have direct data showing the precise role of KPNA2 in glioma, based on the improved outcomes in patients exhibiting elevated expression of MIR517C, we hypothesize that KPNA2 may act as an oncogene in GBM.…”
Section: Discussionmentioning
confidence: 51%
“…Note that the expression loss of MAPK1 a contributing factor for cell-cycle progression (Brunet et al, 1995), decreased cell proliferation as expected, but did not cause full inhibition as found after a KPNA2 knockdown. In line with this, a KPNA2-silencingcaused reduction of cell proliferation was reported for prostate cancer cells as well (Mortezavi et al, 2011). Additionally, KPNA2 gene silencing increased significantly the apoptosis rate of malignant MCF7DKPNA2 cells, which could also explain the decreased viability of MCF7DKPNA2 cells during the migration experiment.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, recent work identified KPNA2 as a potential prognostic marker for the progression of prostate cancer as well as therapy indicator for patients who underwent radical prostatectomy (Mortezavi et al, 2011).…”
mentioning
confidence: 99%
“…16 A relevant biological role of NBS1 in prostate cancer is further supported by immunohistochemical studies describing higher NBS1 expression in cancer as compared to non-neoplastic prostate epithelium. 19 To further evaluate the potential biological and clinical role of NBS1 in prostate cancer, and to search for possible associations with molecularly defined cancer subgroups, a preexisting tissue microarray (TMA) containing 11,152 prostate cancer specimens with follow-up data and attached molecular information was analyzed for NBS1 immunostaining. Our data demonstrate a link of NBS1 immunostaining with morphological and molecular cancer features as well as with PSA recurrence, which is largely driven by KPNA2 expression.…”
mentioning
confidence: 99%